Menakar Digital Marketing Pada Lembaga Pendidikan Pariwisata - Kadek Ardi Permana; Agus Putu Abiyasa (Jurnal Manajemen dan Bisnis, 2019)
The purpose of this study is to find out how the role of digital marketing in the Tourism Education Institute. This research was carried out in tourism education institutions in the Province of Bali that have carried out digital marketing strategies. Given that at this time digital marketing is becoming a trend among businessmen and in educational institutions. Especially now that the millennial generation is looking for information through the internet or accessing various kinds of social media that are currently being loved by young people throughout the country. There are a number of questions given to participants and informants in this study where participants and informants are new students in tourism education institutions. The selection of informants in this study is by using the purposive sampling method and the technique of validating the data using the source triangulation technique. The result of this research is that currently the preferred marketing strategy is in a conventional way where this method is still the favorite way for the public, especially new students to get information about the Tourism Education Institution which they will choose compared to digitalization, which is still an option the second to introduce Tourism Education Institutions to the public, especially new students, is moreover the uneven knowledge and lack of connections from internet networks in the Tourism Institution area which causes this digital marketing to be less optimal.